(untitled) (Biological Sciences - PJSIR, 2025)
The study aimed at examining the nutritional analysis of broken rice (Oryza sativa L.) and bakery products made from it. In current project basmati broken rice was used. Some of the broken rice was used for the nutritional analysis, while rest was ground in the fine rice flour for making biscuits and pancakes. Nutritional analysis showed that the biscuits made with rice flour were rich in protein, fat, fibre and total carbohydrates content, while pancakes made with rice flour was rich in moisture, fat and energy in calorie content. Therefore, we can use broken rice with a mixture of other flours for making bakery products because of their fine taste and gluten free properties.